Bibliotheken gestalten Zukunft Kooperative Wege zur Digitalen Bibliothek - Hutzler, Evelinde; Schröder, Albert; Schweikl, Gabriele (Universitätsverlag Göttingen, 2008)
Libraries are not passive to the rapid and profound digital change. They have recognized and accepted the task and opportunity to actively participate in shaping a sustainable information infrastructure for a modern knowledge society. They use the opportunities of new information technologies to build digital libraries and to expand its service range by offering innovative services. Acknowledged experts from libraries and science in this book give an in-depth insight into current developments in this very important sector for libraries. The topics of the contributions in this volume range of approaches and strategies to improve the information structure of academic libraries on concrete examples of the establishment and development of digital libraries in practice to prospects for future development opportunities and areas of action.